2016
DOI: 10.3390/photonics3030046
|View full text |Cite
|
Sign up to set email alerts
|

Ar+-Implanted Si-Waveguide Photodiodes for Mid-Infrared Detection

Abstract: Abstract:Complementary metal-oxide-semiconductor (CMOS)-compatible Ar + -implanted Si-waveguide p-i-n photodetectors operating in the mid-infrared (2.2 to 2.3 µm wavelengths) are demonstrated at room temperature. Responsivities exceeding 21 mA/W are measured at a 5 V reverse bias with an estimated internal quantum efficiency of 3.1%-3.7%. The dark current is found to vary from a few nanoamps down to less than 11 pA after post-implantation annealing at 350˝C. Linearity is demonstrated over four orders of magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Figure 14 illustrates the basic geometry and spectral response of a Zn-implanted p-i-n detector device seamlessly embedded in an SOI waveguide. Ion implantation also creates lattice defects with optically active trap states such as divacancies, and Si + and Ar + implanted SOI waveguide detectors belong to this category [181,183]. These detectors are fully compatible with standard CMOS fabrication and do not necessitate the introduction of foreign materials in the Si platform.…”
Section: Inmentioning
confidence: 99%
“…Figure 14 illustrates the basic geometry and spectral response of a Zn-implanted p-i-n detector device seamlessly embedded in an SOI waveguide. Ion implantation also creates lattice defects with optically active trap states such as divacancies, and Si + and Ar + implanted SOI waveguide detectors belong to this category [181,183]. These detectors are fully compatible with standard CMOS fabrication and do not necessitate the introduction of foreign materials in the Si platform.…”
Section: Inmentioning
confidence: 99%
“…These photodetectors are fully compatible with standard CMOS process, however, the major limitations of these detectors is their low temperature operation to reduce the thermal noise arising from the transition between close lying energy levels. While Si has bandgap of 1.12 eV but sub‐band gap absorption in the mid‐IR can be introduced either by doping or by forming lattice defects using deep level dopants such as Zn, Ar, Au, S, and Se etc 115,120–123 . Alternatively, energetic ion bombardment can also create lattice point defects with optically active trap states in the bandgap 124 .…”
Section: Candidate Materials For Mid‐ir Waveguide Integrated Detectorsmentioning
confidence: 99%
“…The detector is shown in Figure 2C. Souhan et al 120 studied the linearity, responsivity and thermal stability of Ar + implanted monolithic integrated Si waveguide photodetectors over 2.2‐2.3 μm wavelength range. Results from this study showed a peak responsivity between 20 and 25 mA/W using a reverse bias of 5 V. Recently, incorporation of chalcogenides into Si using femtosecond laser ablation and ion implantation followed by pulsed laser melting have also attracted lot of attention.…”
Section: Candidate Materials For Mid‐ir Waveguide Integrated Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al demonstrated the all-optical modulation of self-standing porous. Correspondingly, it is worth mentioning that Si + and Zn + ion-implanted silicon photodetectors (PDs) can obtain 1.7GHz 3 dB bandwidth [16]- [18]. Recently, silicon-graphene hybrid plasmonic waveguide PD operating at 2 μm has a bandwidth of >20 GHz [19].…”
Section: Introductionmentioning
confidence: 99%